Oligopoly as a Non-Zero-Sum Game - Neisser, H. (Review of Economic Studies, 1957)
Journal Article Oligopoly as a Non-Zero-Sum Game Get access H. Neisser H. Neisser New York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 25, Issue 1, October 1957, Pages 1–20, https://doi.org/10.2307/2296117 Published: 01 October 1957